PROSPECTS FOR THE DEVELOPMENT OF THE FLOWER MARKET OF UKRAINE BASED ON THE MODERN LOGISTICS APPROACH - SHVARTS, Iryna; BEZSMERTNA, Oksana; KRAIEVSKA, Alla; PELESHOK, Anastasia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the pre-war period, the Ukrainian flower industry was very dynamic and developed rapidly. The assortment of goods in retail trade, production technologies, markets and consumer demands were constantly changing, which forced participants to constantly improve. In global markets, new exporters from developing countries are expanding their market share by displacing existing producers. Competition among industry players contributes to the constant improvement of product quality, the introduction of innovations in production and logistics. Supply chain management, which involves the creation of optimal mechanisms of interaction between enterprises of the flower industry, has a great impact on the development of the flower industry as a whole, but at the moment it is not effective enough. In addition, modern enterprises of the flower business of Ukraine suffered significant material, technical and financial losses in connection with the Russian aggression, which requires them to find ways to optimize logistics activities.The article examines the current state of the flower market and examines the factors affecting the formation of the market in Ukraine, identifies the main trends and prospects for the development of the flower business during the full-scale war. Analytical and statistical methods of data processing were used during the research. An analysis of the state of the market was carried out and the activity of the main producer of flower products in Ukraine was characterized. A study of the conditions of logistical transportation of flower products was carried out, the trend of import and export of flowers in Ukraine was studied. Information about participants in the domestic flower industry is presented and problems related to the development of the Ukrainian flower industry and the sale of finished products are identified. The main negative factors affecting the development of the flower market in Ukraine have been determined. The need to use modern logistics concepts in order to optimize the complex of logistics functions of enterprises in the flower industry is substantiated.
Keywords: flowers; floriculture market; logistics concepts; trade; supply chains; import; export; sales